2021
DOI: 10.1111/rsp3.12399
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of manufacturing micro firms' productivity in Ecuador. Do industry and canton where they operate matter?

Abstract: This study aims to identify the productivity determinants of manufacturing micro firms, emphasizing on regional and industrial factors. A cross-classified multilevel model is employed using the Economic Census of 2010 from Ecuador. Results show (90.1%) that the heterogeneity of the total factor productivity of micro formal firms of the manufacturing sector is mainly due to differences across firms. The remaining variation of the TFP is explained to a larger extent by the industrial context (5.8%) than the geog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…To prove this evidence, we perform a formal test ( F test) to assess the equality of these three coefficients, and the results, shown at the bottom of Table 2, indicate that the null hypothesis that the three coefficients are equal is rejected for the three models. In Ecuador, the manufacturing sector is also labor-intensive (Guevara-Rosero, 2021). In addition, the results show that input elasticity is slightly different across the knowledge intensity classification that suggests a nonsignificant heterogeneity among industries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To prove this evidence, we perform a formal test ( F test) to assess the equality of these three coefficients, and the results, shown at the bottom of Table 2, indicate that the null hypothesis that the three coefficients are equal is rejected for the three models. In Ecuador, the manufacturing sector is also labor-intensive (Guevara-Rosero, 2021). In addition, the results show that input elasticity is slightly different across the knowledge intensity classification that suggests a nonsignificant heterogeneity among industries.…”
Section: Resultsmentioning
confidence: 99%
“…De Fuentes et al (2019) point out that smaller firms are more productive compared to larger firms, due to their prompt adaptation to changes required by the market. Guevara-Rosero (2021), in a study about microenterprises, also shows evidence of higher productivity for unipersonal businesses, compared to firms with more than two employees and up to nine employees. For Tocco (2015), the lack of preparation to run a company that is too large or complex can result in increased unit costs of production.…”
Section: Productivity Determinants In the Service Sectormentioning
confidence: 92%
See 2 more Smart Citations
“…Prior works have identified that several factors, such as technical progress, ICT, credit, and firm age, are crucial determinants of the productivity dynamics of food manufacturing companies (Blažková et al, 2020; Chang et al, 2019; Guevara‐Rosero, 2021; Náglová & Pechrová, 2021). However, the existing literature is incomplete or deficient in the sense that it does not reflect the recent development of digitalization in the agrifood sector.…”
Section: Introductionmentioning
confidence: 99%